Method of application protocol for BTR reliability data of wireless computer networks - Дуднік, А. С.; Бондаренко, Ю. В. (Problems of Informatization and Control, 2013)
Wireless computer networks are a relatively new type of computer systems used in the nationaleconomy and the objects of special purpose, they are characterized by diverse natureand high density traffic information is transmitted in a powerful stream of noise, uniformstructure and a large number of integrated network assets with insufficient protection.